Aksjologiczny aspekt probacji. Sens i wymiar solidaryzmu społecznego w procesie reintegracji skazanych (Filozofia Edukacji, 2019)
Traditionally, offenders were eliminated, stigmatized, physically punished, isolated, and, as a result, excluded from society. Today, we are talking about the need for fostering offenders in building their new, non-deviant identities. Instead of forcing them to be subordinated, they should be encouraged to go for changes, to interiorize norms, principles, and values important from the point of view of society. In the article, the sense and dimension of the local environment participation in the probation process of offenders are considered. A theoretical framework for the considerations is the concept of social solidarity. On the basis of the analyses of the principle of subsidiarity and the concept of citizen society an attempt to grasp the ideological motives animating pro-social activities within the resocialization process. Also, an actual picture of such activities in the probation practices is presented.